Existential Dimensions in the Socio-Legal Sphere: Introduction - Ronnie Lippens; James Hardie-Bick (Oñati Socio-Legal Series)
This introduction addresses the relevance of existentialist philosophy for understanding the indeterminacies and instabilities of late-modern society. Whilst existentialist thought is often misunderstood and subsequently unexplored, all the contributors to this special edition accept the basic premise that human existence is inescapably contingent and indeterminate. This introduction provides a short overview of the articles and reflects on themes such as destabilization and reintegration. All the articles are based on contributions to the workshop 'Law, Jurisprudence, Governance and Existential Indeterminacy', held at the International Institute for the Sociology of Law, Onati, Spain, 23-24 May 2013.